2003
DOI: 10.1007/s11748-003-0053-0
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex viral pneumonia after coronary artery bypass grafting

Abstract: We report a case of herpes simplex viral (HSV) pneumonia as a post-CABG pulmonary complication in a 70-year-old man. Chest radiography on postoperative day 9, showed a glass-like shadow and pleural effusion in the left lung field, and the man's condition began deteriorating rapidly. Bronchofiberscopy to detect the pathogen and a bronchoalveolar lavage with polymerase chain reaction (PCR) yielded a definitive diagnosis of HSV pneumonia. Once therapy with acyclovir was begun, his condition improved markedly. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 7 publications
2
15
0
3
Order By: Relevance
“…To date, HSV bronchopneumonitis has mostly been described in patients taking immunosuppressants [20,21], with ARDS [22], after surgery [23][24][25][26], or burn victims [27,28]. It was recently demonstrated that HSV bronchopneumonitis was frequently detected among nonimmunocompromised patients with prolonged mechanical ventilation; in our monocentric study, we found that out of 201 patients suspected of having ventilatorassociated pneumonia (VAP), 42 (21%) were diagnosed with HSV bronchopneumonitis.…”
Section: Herpesviridaementioning
confidence: 67%
“…To date, HSV bronchopneumonitis has mostly been described in patients taking immunosuppressants [20,21], with ARDS [22], after surgery [23][24][25][26], or burn victims [27,28]. It was recently demonstrated that HSV bronchopneumonitis was frequently detected among nonimmunocompromised patients with prolonged mechanical ventilation; in our monocentric study, we found that out of 201 patients suspected of having ventilatorassociated pneumonia (VAP), 42 (21%) were diagnosed with HSV bronchopneumonitis.…”
Section: Herpesviridaementioning
confidence: 67%
“…Recently, the polymerase chain reaction (PCR) has been utilized, providing a faster (i.e., approximately 24 h) diagnostic technique with high sensitivity and specifi city. 4,5,14 In the near future, PCR may become the gold standard used to diagnose HSV pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, clinical reports of HSV pneumonia after cardiac surgery are rare. [3][4][5] We report a patient who was diagnosed with HSV pneumonia and successfully treated with acyclovir during the postoperative period of mitral valve replacement (MVR).…”
Section: Introductionmentioning
confidence: 99%
“…In that study, reactivation was asymptomatic in 56% of the patients, but associated with herpetic labial ulceration or gingivostomatitis in 48 (44%) of 109 patients with oropharyngeal viral reactivation. HSV bronchopneumonitis was initially described in immunocompromised patients [28,29], but other data showed that it can occur in nonimmunosuppressed patients with acute respiratory distress syndrome (ARDS) [13], after surgery [9,14,30,31] or in burn victims [10,32]. However, HSV detection in the lower airways does not mean viral pulmonary parenchymal disease; HSV detection might reflect airway contamination by saliva, tracheobronchial reactivation without parenchymal involvement or true HSV bronchopneumonitis [8,27].…”
Section: Role Of Herpes Simplex Virus In Nosocomial Pneumoniamentioning
confidence: 99%